Percepção de fala de idosos usuários de próteses auditivas com diferentes microfones e algoritmo redutor de ruído - Santos, Sinéia Neujahr dos (2015)
OBJECTIVE: To evaluate speech recognition in noise on elderly people, new users of hearing aids with directional microphones and noise reduction, and check which feature provides better speech intelligibility; to investigate the perception of performance of elderly people, with the use of hearing aids with different settings, and check for relationship with speech recognition in noise; and to identify the best performance of the elderly in speech tests and analyze which aspects influence the results: adjustments of the hearing aids and / or degree and configuration of hearing loss, performance on cognitive screening and listening skills. METHODS: Participated 36 individuals between 60 and 87 years with mild to moderately severe sensorineural hearing loss. Brazilian Portuguese Sentences Lists test was applied, in free field, obtaining the sentence recognition indexes in noise (SRIN) with hearing aids, with four different settings: omnidirectional microphone; noise reduction and omnidirectional microphone; directional microphone and the noise reduction and directional microphone. As for the self-perception with different schedules, a questionnaire was applied with the use of hearing aids, developed for this research. To Investigate the factors that could influence the elderly's performance with the use of hearing aids, it was considered: tritonal average 500.1000 and 2000 Hz and 3000, 4000 and 6000 Hz; Mini mental state examination results, dichotic digits test and standard duration. RESULTS: When speech and noise focused 0°/0° azimuth, SRIN scores were 76.74% using omnidirectional microphone; 84.95% with noise reduction and omnidirectional microphone; 84.40% directional microphone; and 86.63% with noise reduction and directional microphone. When noise focused 0°/180°, median SRIN were 77.4% with omnidirectional microphone use; 83.79% with noise reduction and omnidirectional microphone; 89.46% with directional microphone; and 91.99 with noise reduction and directional microphone. There was no correlation between the SRIN obtained with the different settings and the self- perception questionnaire score with the use of hearing aids. Since clinical evaluations tend to show conflicting results regarding those found in self-assessment questionnaires, objective and subjective measures must be linked to the verification of possible benefits provided by the directional microphone and noise reduction. When speech and noise came from the same direction (0/0 ° azimuth), there was no predominance of the settings in the best performance in SRIN. In the condition that the noise focused behind the subject (0/180 ° azimuth), the directional microphone and the associated noise reduction were essential for the best performance. There was a correlation between the SRPRN 0/0 ° and the dichotic digits test. CONCLUSION: Better results were seen with the noise reduction and directional microphone use in both situations evaluation, however, the situation with noise at 0°/180° the directional microphone provided a more satisfactory performance. There was no relationship between the performance of self-perception questionnaire with the use of hearing aids and speech recognition in noise, with different possibilities of adjustment. The ability of figure-ground for verbal sounds showed influence the communicative performance of the elderly user of hearing aids, when speech and noise came from the same direction. But when speech and noise are spatially separated, the directional microphone and the associated noise reduction helped the individual to respond the stimuli presented more efficiently.